Influence of Discount and Customer Rating on Impulse Buying: A Study on Gen Z TikTok Shop Users in Bandar Lampung - Saputra, Rahmat Dwi; Agung P, Maulana; Septiani, Winda (Journal of Business Management and Economic Development, 2025)
TikTok Shop has emerged as a highly favored e-commerce platform among Generation Z due to its engaging and interactive shopping experience. However, the platform's ease of access and frequent usage can also lead to impulsive buying behavior. On the other hand, large discounts and high customer ratings are its own attractions that influence impulse buying. Generation Z who grew up in this digital era tend to rely on TikTok Shop as their main online shopping platform, especially in Bandar Lampung where digital growth is relatively high. This research aims to test how much influence discounts and customer ratings have on impulsive purchases in TikTok shop. Quantitative approach and explanatory research design were used in this study. The process of data collection in this study was carried out by distributing questionnaires to a total of 100 respondents who are categorized as members of Generation Z and are active users of TikTok Shop in the city of Bandar Lampung. The selection of respondents was done using a purposive sampling technique, which means participants were chosen based on specific criteria relevant to the research objectives. Once the data was collected, it was processed and analyzed using multiple linear regression analysis to examine the relationship between the variables studied. The findings of this research indicate that both discount offers and customer ratings significantly and positively affect impulsive buying behavior. This influence is evident not only when these variables are considered individually but also when they are examined simultaneously. Among the two, discounts exert the strongest influence, indicating that price reductions are more effective in driving impulsive purchasing behavior. Together, these two variables account for 36.8% of the variance in impulse buying, the remaining 63.2% was effect by other factors that were not studied by the researchers in this research.